Siti Akila Enterprise / Nurul Wajihah Sami'on ... [et al.] - Sami'on, Nurul Wajihah; Jauhari, Nur Syazana; Rosman, Nurul Aqilah Syahirah; Amad, Nur Afira; Mohamad Nasir, Nurul Nashtasha; Yacob, Syamimi Syasya (2019)
Siti Akila Enterprise is a company 100% of bumiputra by Encik Halim which produces bakery products and frozen foods. The name of Siti Akila is taken from his youngest daughter’s name. The company has started his business since 2004 until now and it has been for 15 years. He run his business at TL 72, Kampung Parit Haji Idris, 84800 Bukit Gambir, Ledang, Johor. The operation of his factory start from 7:30 a.m until 2:00 p.m. He run this business with his wife and around 10 workers who help them to produce the products. This company has successfully marketed their products through agent’s sale and agent appointed in every district and state entire Malaysia.